Social Media Flexing, Self-Presentation, and Conspicuous Consumption: A Phenomenological Study of Generation Z University Students - YUNIAR MUJIWATI; HANUM FITRI HANIFAH (Universitas PGRI Kanjuruhan Malang, 2026)
The phenomenon of